Physiological quality and antioxidant enzymes activity in eggplant seeds with different ages and resting periods after harvest - Aguilar, Ariel Santivañez [UNESP] (2023)
Constant changes during the seed maturation process affect its final quality and the post-harvest fruit resting, which can improve seed physiological quality. Therefore, the objective of this study was to evaluate the physiological and enzymatic activities of eggplant seeds extracted from fruits harvested at different ages and resting periods after harvest. Fruits were harvested presenting different colors at 40, 50, 60, and 70 days after anthesis (DAA) and rested for 0 (freshly harvested fruits), 10, and 20 days. The experimental design was set as completely randomized, with four replications and evaluated seeds extracted from six fruits per plot. The resting periods in eggplant fruits harvested at less than 60 DAA improved the mass of 1000 seeds, germination, vigor, and protein content. Seeds with higher germination and vigor presented lower dismutase (SOD), catalase (CAT), and peroxidase (POX) enzymatic activity. The results indicated that the ideal moment of eggplant harvest for seed production is when the fruit reaches the yellowish-brown color corresponding to about 60 DAA; however, if the eggplant fruit is harvested earlier (40 or 50 DAA), it has to rest for about 10 to 20 days to achieve high physiological quality (germination and vigor).